Teaching methods in public relations courses: challenges and perspectives for higher education - Ferrari, Maria Aparecida; Martins, Juliane; Theodoro, Victor (Organicom, 2020)
The teaching process of Brazilian public relations university programs has long been neglected by academic research, which is evidenced by the scarcity of available bibliography. The objective of this study is to present the teaching methods currently used for classroom teaching. Interviews were conducted with public relations academics and coordinators from five Brazilian regions. Results reveal the current status, challenges and perspectives regarding the use of technologybased tools for the teaching of Public Relations.